A randomised placebo-controlled Phase III multicentre trial: low-dose intravenous immunoglobulin treatment for long-standing complex regional pain syndrome (LIPS trial) - Andreas Goebel; Jatinder Bisla; Roy Carganillo; Claire Cole; Bernhard Frank; Rima Gupta; Mairi James; Joanna Kelly; Candy McCabe; Holly Milligan; Caroline Murphy; Nick Padfield; et al. (Efficacy and Mechanism Evaluation, 2017)
Background: Complex regional pain syndrome (CRPS) is a rare, severe post-traumatic pain condition affecting distal limbs. Patients who do not spontaneously improve in 12 months are classed as having ‘long-standing CRPS’ and often cannot be effectively treated, leading to a poor prognosis. CRPS is associated with functional autoantibodies. Two small trials, including a randomised controlled trial, have suggested that low-dose intravenous immunoglobulin (IVIg) may be an effective treatment for some patients. Objective: We hypothesised that low-dose IVIg is effective for reducing pain in long-standing CRPS. Methods: A randomised, double blinded placebo-controlled multicentre trial in seven UK pain management centres. Patients were eligible if they had moderate or severe long-standing CRPS that they had experienced for up to 5 years. Participants were randomly allocated to receive 0.5 g/kg IVIg, the active intervention, or visually indistinguishable 0.1% albumin in saline placebo. Randomisation was initiated by study sites via an independent online randomisation system and was 1 : 1 with varying block sizes, stratified by study centre. Participants, investigators and assessors were blinded to group assignment. The study drug/placebo was infused intravenously at the study centres on day 1 and day 23 after randomisation. The primary outcome was the 24-hour average pain intensity between day 6 and day 42, on an 11-point (0–10) numeric rating scale, compared between the groups. Outcomes were analysed using a mixed-effects regression model that used 37 measurements of pain intensity (the primary outcome) per participant. All patients who received an infusion and provided any outcome were included in the intention-to-treat analysis. Results: A total of 111 patients were recruited and assigned between 27 August 2013 and 28 October 2015. Three patients were excluded because they had been inappropriately randomised, five patients were withdrawn from the primary analysis because they provided no outcomes and 103 patients were analysed for the primary outcome. The average pain score in the IVIg group was 0.27 units (95% confidence interval –0.24 to 0.80 units) higher than in the placebo group. Therefore, there is no significant evidence of a treatment effect at the 5% level and there was no significant difference between groups. Six serious adverse events but no suspected unexpected serious adverse reactions were reported during the blinded and open-label phase. Conclusion and future work: Low-dose immunoglobulin was not effective in relieving pain in patients with moderate to severe CRPS of 1–5 years’ duration. Better drug treatments for long-standing CRPS are urgently required. Trial registration: Current Controlled Trials ISRCTN42179756. Funding: This project was funded by the Efficacy and Mechanism Evaluation programme, a Medical Research Council and National Institute for Health Research partnership. Additional funding was obtained by the Pain Relief Foundation. Biotest UK Ltd provided the active study medication at no cost.